Role of waist circumference, body mass index and high-sensitivity C-reactive protein in pediatric steatotic liver disease: A cross-sectional study - Qiaoling Wu; Yongmei Peng; Chundan Gong (Annals of Hepatology)
Introduction and Objectives: Relationships and interactions among waist circumference (WC), body mass index (BMI) and high-sensitivity C-reactive protein (hs-CRP) with steatotic liver disease (SLD) in children have rarely been studied as a whole. We aimed to investigate the association among WC, BMI and hs-CRP with SLD and its related metabolic indictors. Materials and Methods: A total of 10,776 children aged 10–15 years were screened in our study. Anthropometric data, biochemical parameters and ultrasound assessments were collected. Metabolic indictors between children with and without SLD were compared. The correlation of waist circumference Z score (ZWC), body mass index Z score (ZBMI) and hs-CRP with SLD and its related metabolic indictors, and the interactive effect between ZWC with hs-CRP and ZBMI with hs-CRP upon SLD, respectively, was tested. Results: A total of 543 children with normal BMI (n = 287) and high BMI (n = 256) were examined. Hs-CRP, ZWC and ZBMI were all found to significantly correlate with SLD and its related metabolic indexes. The interaction effect analysis showed that ZWC and male was independent risk factor of SLD with OR (95 %CI) of 23.431 (7.253, 75.697) and 7.927 (2.766,22.713), respectively, whereas the same effect wasn't found in ZBMI. The cut-off value of ZWC for the prediction of SLD was 1.494 and 1.541 in boys and girls, respectively. Conclusions: Increased WC, BMI and hs-CRP exerts adverse effect in pediatric SLD and its related metabolic indictors. WC and male gender could be independent risk factors for SLD, and WC was a powerful index for the prediction of SLD in children aged 10–15 years.